2015
DOI: 10.1093/cid/civ710
|View full text |Cite
|
Sign up to set email alerts
|

Mathematical Modeling to Assess the Drivers of the Recent Emergence of Typhoid Fever in Blantyre, Malawi

Abstract: Background. Multiyear epidemics of Salmonella enterica serovar Typhi have been reported from countries across eastern and southern Africa in recent years. In Blantyre, Malawi, a dramatic increase in typhoid fever cases has recently occurred, and may be linked to the emergence of the H58 haplotype. Strains belonging to the H58 haplotype often exhibit multidrug resistance and may have a fitness advantage relative to other Salmonella Typhi strains.Methods. To explore hypotheses for the increased number of typhoid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
66
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 55 publications
(70 citation statements)
references
References 23 publications
(33 reference statements)
4
66
0
Order By: Relevance
“…This concurs with prevailing conceptualisation[64,65], and experimental study [66] as well as recent models used to estimate vaccine impact [21,67] and elucidate transmission determinants in Malawi [23]. Papua New Guinea saw a similar upturn in typhoid notifications in the 1980-90s, also from a low-level, sporadic baseline, [68] with rise in population O antigen also observed [69], suggesting an overall increase in transmission; longitudinal seroepidemiology may likewise be informative in Fiji.…”
Section: Discussionsupporting
confidence: 89%
“…This concurs with prevailing conceptualisation[64,65], and experimental study [66] as well as recent models used to estimate vaccine impact [21,67] and elucidate transmission determinants in Malawi [23]. Papua New Guinea saw a similar upturn in typhoid notifications in the 1980-90s, also from a low-level, sporadic baseline, [68] with rise in population O antigen also observed [69], suggesting an overall increase in transmission; longitudinal seroepidemiology may likewise be informative in Fiji.…”
Section: Discussionsupporting
confidence: 89%
“…In Africa, crowded cities and significant numbers of immunocompromised people are potential factors that could enhance the dissemination of clones. Interestingly, mathematical modeling to evaluate the impact of these risk factors found that increased pathogen transmission rates and longer durations of infectivity were even more important factors enabling spread, (Pitzer et al, 2015 ). Therefore, whilst unjustified antimicrobial use contributes to resistance, inadequate access to appropriate antibiotics when needed could also exacerbate the problem.…”
Section: Discussionmentioning
confidence: 99%
“…Recently Chikungunya and Zika 6 have provided examples of how outbreaks can occur outside the disease's historic geographical confines, and increasing drug resistance can lead to spread of bacterial diseases including enteric fevers in areas they were not previously common. 7 Epidemics of these diseases in the tropics may be associated with increased numbers of cases among travellers. Malaria remains the most common potentially fatal imported infection in the UK and treatment by clinicians experienced in managing imported infections has been shown to be associated with better outcomes.…”
Section: Introductionmentioning
confidence: 99%